Synthesis and characterization of PLA-Chitosan-ZnO composite for packaging biofilms - Rihayat, Teuku; Suryani, Salim; Fitriyani, C. N.; Aidy, Nurhanifa; Siregar, J. P.; Jaafar, J.; Cionita, Tezara; Fitria, Fitria (Institute of Physics Publishing, 2020)
This research was conducted to improve the characteristics of PLA-Chitosan-ZnO composites. Composites are synthesized from the matrix of Poly lactic acid by modifying Chitosan and Zinc oxide (ZnO) fillers. The purpose of this study was to look at the mechanical, thermal and morphological characteristics seen from the composite. Basically, the bond between PLA and CS is very weak, so to increase the strength of the bond by entering ZnO; thus advancing overall quality (mechanical, thermal and water absorption) of composites (PLA / CS / ZnO). The mechanical properties of composites are enhanced by the addition of ZnO NP into the PLA / CS matrix. However, the tensile strength, modulus, and breakout extension increased to 2wt% of ZnO NP loading but decreased when ZnO NP content increased by 3wt%. This is consistent with the dispersion of homogeneous ZnO particles in the PLA matrix. Combining ZnO particles increases PLA thermal stability. Thus, ZnO has been shown to have potential as an amplifier in biocomposite synthesis with better integrity, although other approaches, such as the use of compatibilizers in ZnO surface modification, will be needed to improve PLA properties simultaneously. The results obtained in this work can be used on environmentally friendly films.